BIOGRAPHY AS A LEARNING RESOURCE IN MULTICULTURAL EDUCATION: A LITERATURE REVIEW STUDY IN THE CONTEXT OF INCLUSIVE CHARACTER FORMATION - Ahmad Fakhri Hutauruk; Indra Prasetia; Muhammad Arifin (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2026)
This study examines the potential of biography as a learning resource in multicultural education for strengthening students’ inclusive character. Using a literature review supported by bibliometric mapping with VOSviewer, the study analyzed publication metadata obtained through Publish or Perish from Google Scholar within the 2016–2026 period. The review focused on the relationship between biography, education, literature, teaching, schools, students, and the Indonesian context. The findings show that education is the most central concept in the mapped literature, while biography appears as a relevant but still underdeveloped theme. Biography can function as a narrative-based pedagogical medium that introduces students to lived experiences, cultural diversity, moral struggle, empathy, tolerance, and social responsibility. The study concludes that biography-based learning has strong relevance for multicultural education, particularly in plural societies such as Indonesia, but further empirical research is needed to test its classroom implementation and impact on students’ inclusive attitudes and character development directly.